Evaluation of young elite soccer players food intake on match day and highest training load days - Silvério Granja, D.; Cotovio, R.; Pinto, R.; Borrego, R.; Mendes, L.; Carolino, E.; Macedo, F.; Ferreira, D.; Caetano, C.; Mendes, B. (Journal of Human Sport & Exercise, 2017)
It is crucial to ensure an adequate nutritional support for young soccer players under high physical stress situations, including match days and high training load days. Therefore, this study aimed to investigate the dietary intake of young male soccer players from a Portuguese first league soccer club, both on match day and on the highest training load day of the week. All players recorded their ingestion at these moments for 3 consecutive weeks, by completing a food diary and making a photographic record. On match day, the intake of carbohydrates (5.2 ± 0.6 g/kg.d), proteins (2.1 ± 0.2 g/kg.d), and fats (1.0 ± 0.2 g/kg.d) represented 55.1 ± 5.0 %, 22.3 ± 1.52 %, and 23.9 ± 5.1%, respectively, of the average daily energy intake. Regarding the highest training load day, the intake of carbohydrates (5.2 ± 0.9 g/kg.d), proteins (2.0 ± 0.3 g/kg.d), and fats (1.0 ± 0.3 g/kg.d) represented 54.8 ± 5.3 %, 21.8 ± 1.8 %, and 24.6 ± 4.6 %, respectively. There were no statistically significant differences between intakes during match day and on the highest training load day, for all the variables analyzed, except for percentage of fat intake (Energy intake p = 0.873; Protein p = 0.335; Carbohydrates p = 0.814; Fat p=0,000). The results obtained are in line with previous research and reveal that energy and carbohydrate intake are below the recommendations for this population.